Hubungan antara Efikasi Diri dengan Kecurangan Akademik pada Siswa Kelas XI IPA dan IPS di SMA Negeri I Tanjung Batu - Rezi Tiana Permatasari; Ema Yudiani; Fajar Tri Utami (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study discusses the relationship of self-efficacy and academic cheating in class XI science and social studiesat SMA Negeri 1 Tanjung Batu. This study aims to determine whether there is a relationship of self-efficacydengan academic cheating in class XI science and social at SMA Negeri 1 Tanjung Batu. By using quantitativeresearch. The sample used in the study amounted to 123 student. Data analysis method used is product momentanalysis. Based on the result of research that has done, it can be concluded that there is a no relationship betweenself-efficacy and academic cheating, this is evidenced by the result of the correlation coefficient which show thenumber -0.156 with a sig. 0.085 where p > 0.05. Meaning that the higher the self-efficacy, the lower the academiccheating conversely the lower of self-efficacy the higher the academic cheating.